Affective intensities of single lives: An alternative account of highs and lows of everyday life - Kolehmainen Marjo; Lahti Annukka; Kinnunen Anu (United Kingdom, 2022)
The number of people living without a partner is growing globally, but this demographic shift has barely disrupted the tenacity of the couple norm. Researchers have identified several concrete mechanisms of singlism – practices that feed the unequal treatment of single people. Nevertheless, there is still a need to develop an understanding of how singlism operates affectively. To provide insights into the affective intensities of single lives, we incorporate the notion of affective inequality into an analysis of singlehood and temporality, bringing together a range of data sets to further develop this idea. We examine the varying affective and psychic experiences that characterise how singles feel about their singlehood, how they experience the current moment and how they view the future. We argue that these experiences are shaped by singlism, and that affective inequalities and affective privileges co-condition the possibilities for different types of relationships.